Evaluation of CSR Management "Synergy: Rising Together" to Increase SMEs Literacy - Muhammad Hafiz Nurul Haqqi (JKG (Jurnal Komunikasi Global))
PT Angkasa Pura Logistics (APLog) Public Relation divisions launched the "Synergy: Rising Together with SMEs" CSR program to improve SMEs financial management, digital marketing, and Indonesian National Standards (SNI). However, the program lacks clear success indicators and does not fully address the economic, social, and environmental pillars of CSR or the Triple Bottom Line framework. This study evaluates the program’s effectiveness using Broom and Sha’s Four Stages of Public Relations framework: problem definition, planning, implementation, and evaluation. A qualitative descriptive approach was used, with data collected through in-depth interviews and document analysis involving SMEs participants from Bekasi, Bogor Jember, mentors, and the Public Relations Manager. Findings highlight challenges in planning, inconsistent execution, and insufficient follow-up, limiting the program’s long-term impact. The study emphasizes the need for clear success indicators, practical skill-building, and adherence to CSR principles sustainability, accountability, and transparency. These improvements could enhance the program's effectiveness and align it more closely with best practices in CSR, ensuring its long-term impact and sustainability.